OPHIOLITIC CHROMITITES FROM THE KAHRAMANMARAŞ AREA, SOUTHEASTERN TURKEY: THEIR PLATINUM-GROUP ELEMENTS (PGE) GEOCHEMISTRY, MINERALOGY AND Os-ISOTOPE SIGNATURE - Uysal, Ibrahim; Zaccarini, Federica; Garuti, Giorgio; Meisel, Thomas; Tarkian, Mahmud; Bernhardt, Heinz Jürgen; Sadiklar, Münür Burhan (Ofioliti, 2007)
Mantle-hosted podiform chromitites from ophiolites of the Kahramanmaraş area (south-eastern Turkey), have been investigated with ragard to the chromite composition, Platinum-group elements (PGE) concentration and mineralogy, as well as Os-isotope geochemistry. Chromitites vary from Al-rich to Cr-rich, however they indifferently display enrichment in Os-Ir-Ru over Rh-Pt-Pd, with concentrations of PGE lower than 510 ppb. Consistently, the most abundant Platinum-group minerals (PGM) are Ru-Os-Ir sulfides and alloys with subordinate Ir-Ru-Rh sulfarsenides and one grain of unidentified Pd-Sb phase. Textural relationships indicate that the PGM sulfides and alloys are mostly magmatic in origin, i.e. formed at high temperature prior to or concomitant with the crystallization of chromite, whereas the sulfarsenides and the Pd bearing minerals were formed during post-magmatic processes. The Kahramanmaraş chromitites display relatively high Re/Os ratios, that coupled with error-chron calculated ages, point to a mixing of mantle-derived Os with Os from a source characterized by a relatively high radiogenic signature, possibly subduction-related fluids. If the genesis of the Kahramanmaraş ophiolites is related to subduction, the concomitant presence of Al-rich and Cr-rich chromitites suggests chromite precipitation from melts varying in composition from MORB-like backarc basalts (Al-rich chromite) to boninites (Cr-rich chromite). The geochemical and mineralogical data indicate that most of the Kahramanmaraş chromitites have low PGE potential, due to low PGE concentration, small size of the PGM grains, and predominance of Ru-Os-Ir over Rh-Pt-Pd.Only one sample from Elbistan, exceptionally, was found to have a pronounced positive Pt anomaly, up to 99 ppb, that is supported by identification of magmatic Pt specific phases. Genetic relationships of this chromitite with the others in the area are still unknown. This chromitite represents a potential target for Pt recovery, such that detailed study of the Pt mineralogy, distribution in the chromite ore, and identification of the magmatic sources of Pt, and the mechanisms of Pt concentration, may be useful tools to future exploration in the Kahramanmara` ophiolite.